PSYCHOANALYSIS OF “JENNIE GERHARDT” BY THEODORE DREISER - Baqoyeva Muhabbat Qayumovna; Aminjonova Muattar Odiljon qizi (American Journals, 2023)
This article gives information about psychoanalytic method, its origin, its significance in literature. An overview of this article will help in your understanding of psychoanalytic theory. A part from this, it discusses the psychoanalysis of “Jennie Gerhardt” by Theodore Dreiser.
Keywords: psychoanalytic method, critic, protagonist, prototype, trauma, the bourgeoisie, Sigmund Freud, the id, the ego, the superego, the Oedipus complex.